The influence of the timing of planting on the productivity of buckwheat - Ульянченко, М. С. (Scientific Progress & Innovations, 2018)
The set of optimal sowing dates of the buckwheat is to the actual value on the background of unstable weather of the springtime. In the article, six species of buckwheat (Fagopyrum esculentum Moench) of domestic breeding: Yaroslavna, Slobozhanka, Ruslana, Ukrainka, Krupynka, SIN-3/02 were studied experimentally, depending on the time of sowing in conditions of unstable moisture of the Central Forest-Steppe. For research, conventional methods and special methods were used: productivity of buckwheat varieties and analysis of grain material by the elements of productivity were determined after purification of the grain by air separation method and converted to a standard 14 % moisture content. For the 2015 conditions it has been established that the elements of the buckwheat productivity: the size and number of grains from the plant have a significant effect on the formation of the productivity of the crop. By weight of 1000 grains, Krupynka variety was distinguished at early term sowings; significant lower values ​​were obtained for this variety in Slobozhanka and Ukrainka, respectively for sowing in the first and second terms. All other varieties according to grain size had an average value. The lines of sowing of the variety SIN-3/02 did not influence the elements of productivity. In the conditions of 2016, the varieties Yaroslavna, Ruslana and Krupynka were distinguished by grain size for early and medium term sowing. All varieties put on the study ensured a higher grain size in early sowing, with the exception of Yaroslavna and Ukrainka varieties. According to the results of two-year studies, it has been determined that early varieties of buckwheat Yaroslavna and Ruslana should be sown from the middle of the first decade of May. Sloboda and Krupynka grades produce the highest seed yields in the first and second lines. The exact effect of the sowing date on this indicator in the varieties SIN-3/02 and Ukrainka was not detected.